Development of the Human Placenta and Fetal Heart: Synergic or Independent? - Burton, Graham J.; Jauniaux, Eric (Frontiers in Physiology, 2018)
The placenta is the largest fetal organ, and toward the end of pregnancy the umbilical circulation receives at least 40% of the biventricular cardiac output. It is not surprising, therefore, that there are likely to be close haemodynamic links between the development of the placenta and the fetal heart. Development of the placenta is precocious, and in advance of that of the fetus. The placenta undergoes considerable remodeling at the end of the first trimester of pregnancy, and its vasculature is capable of adapting to environmental conditions and to variations in the blood supply received from the mother. There are two components to the placental membranes to consider, the secondary yolk sac and the chorioallantoic placenta. The yolk sac is the first of the extraembryonic membranes to be vascularized, and condensations in the mesenchyme at ~17 days post-conception (p.c.) give rise to endothelial and erythroid precursors. A network of blood vessels is established ~24 days p.c., with the vitelline vein draining through the region of the developing liver into the sinus venosus. Gestational sacs of early pregnancy failures often display aberrant development of the yolk sac, which is likely to be secondary to abnormal fetal development. Vasculogenesis occurs in the villous mesenchyme of the chorioallantoic placenta at a similarly early stage. Nucleated erythrocytes occupy the lumens of the placental capillaries and end-diastolic flow is absent in the umbilical arterial circulation throughout most of the first trimester, indicating a high resistance to blood flow. Resistance begins to fall in the umbilico-placental circulation around 12–14 weeks. During normal early pregnancy the placental capillary network is plastic, and considerable remodeling occurs in response to the local oxygen concentration, and in particular to oxidative stress. In pregnancies complicated by preeclampsia and/or fetal growth restriction, utero-placental malperfusion induces smooth muscle cells surrounding the placental arteries to dedifferentiate and adopt a proliferative phenotype. This change is associated with increased umbilical resistance measured by Doppler ultrasound, and is likely to exert a major effect on the developing heart through the afterload. Thus, both the umbilical and maternal placental circulations may impact on development of the heart.